2017
DOI: 10.5535/arm.2017.41.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Heart Rate Measurement Using Smartphones During Treadmill Exercise in Male Patients With Ischemic Heart Disease

Abstract: ObjectiveTo evaluate the accuracy of a smartphone application measuring heart rates (HRs), during an exercise and discussed clinical potential of the smartphone application for cardiac rehabilitation exercise programs.MethodsPatients with heart disease (14 with myocardial infarction, 2 with angina pectoris) were recruited. Exercise protocol was comprised of a resting stage, Bruce stage II, Bruce stage III, and a recovery stage. To measure HR, subjects held smartphone in their hands and put the tip of their ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The use of a smart phone camera as PPG sensor can provide an acceptable agreement for some HRV indices when compared with ECG, 22 but there are increasing differences in HRV and HR detection in the setting of movements or exercise 42 . This is because the application algorithm is cancelled in the fi ltering process of inaccurate signals as well as due to the diffi culty of stabilizing the fi ngertip on the camera while exercising.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a smart phone camera as PPG sensor can provide an acceptable agreement for some HRV indices when compared with ECG, 22 but there are increasing differences in HRV and HR detection in the setting of movements or exercise 42 . This is because the application algorithm is cancelled in the fi ltering process of inaccurate signals as well as due to the diffi culty of stabilizing the fi ngertip on the camera while exercising.…”
Section: Hrv Fundamentalsmentioning
confidence: 99%
“…However, despite the importance of this factor, we found only one study in 16 male ischemic patients measuring the accuracy of a smart phone derived pulse rate versus ECG, where an excellent correlation was found at rest, which was slightly deteriorated during exercise. 42 2. Respiration: Since respiration alters the intrathoracic pressure and causes blood fl ow variations in both the veins the DC component of the PPG waveform shows minor changes with respiration.…”
Section: Parameters Involved In Ppg Measurementsmentioning
confidence: 99%
“…11 These findings were similar to a recent study done by Lee et al, where they tested the accuracy of a smartphone application in ischemic heart disease's patients, and they concluded that the accuracy of measured HR from a smartphone was almost overlapped with the measurement from the Holter monitor in resting stage and recovery stage, but measurements error increased as the exercise intensity increased. 21 This issue was also seen in a study using HR wrist-watch monitoring where it did provide valid HR readings at rest and during walking and light jogging but lose ability at higher treadmill speed. 3 Although the findings are encouraging, few limitations that have been noted in this study; these include an unequal gender distribution and a small number of subjects involved in this study which may not represent the general population.…”
Section: Discussionmentioning
confidence: 93%
“…This is in agreement with other observations that the Holter-derived HRV is in parallel with data obtained from other wearable devices capturing RR intervals either from PPG or from other methods at rest and/or at exercise. [25][26][27] The fact that IBI showed a lower specificity to Holter's R-R may be due to the different sampling rate of BVP (64Hz) which is much less than that of ECG (125 to 250 Hz), obviously implying less events detection ability of the PPG devices. 5 Additionally, Bland-Altman analysis was used because the correlation coefficient quantifies only the correlation between two quantities and not their agreement and therefore high correlation does not necessarily mean a close agreement.…”
Section: Discussionmentioning
confidence: 99%